Economic Impacts of Weather Forecast Based Advisories on Vegetable Crops in Mid-hills of Himachal Pradesh, India - Ayush; Singh, Mohan; Bhardwaj, S. K.; Jattan, Priyanka (International Journal of Bio-resource and Stress Management, 2026)
The present investigation was conducted from January, 2022 to December, 2023 in Solan district of Himachal Pradesh under the Department of Environmental Science, Dr. Y.S. Parmar University of Horticulture and Forestry, Nauni, Himachal Pradesh, India to evaluate the economic impact of Agromet Advisory Services (AAS) on major vegetable crops in the mid-hill region. Five blocks, namely Solan, Kandaghat, Dharampur, Kunihar and Nalagarh were selected for the study. From each block, ten AAS adopters and ten non-AAS farmers were randomly selected, making a total sample of 100 farmers. Forecast verification for the period 2016–2023 revealed that the highest annual usability was observed for morning relative humidity (79.4%), followed by minimum temperature (77.0%) and rainfall (73.8%), indicating the reliability of medium-range weather forecasts for farm-level applications. The economic analysis showed that AAS adopters achieved significant savings in input cost (6–8%) due to need-based irrigation, optimized fertilizer application and timely plant protection measures. Consequently, higher net returns were recorded in tomato (11.1%), capsicum (10.3%), cauliflower (9.8%) and pea (8.9%) compared to non-AAS farmers, who experienced net losses ranging from 9 to 12% under similar climatic conditions. The advisories also helped in reducing weather-induced risks, improving resource-use efficiency and enhancing crop productivity. The study clearly indicates that the integration of weather-based agromet advisories into farm management decisions enhances economic profitability, strengthens climate resilience and promotes sustainable vegetable production in the mid-hill agro-ecosystem of Himachal Pradesh.